Evaluation of industry tendencies in Uzbekistan - Radjabov Bunyod Abduhalilovich (Indonesian Journal of Innovation Studies, 2019)
The article proposes a method for assessing trends in industrial development in Uzbekistan. The least-squares method of the regression model was used to estimate industry development trends. Development trends are assessed based on the index of change in the final and theoretical values of industrial production.